Evaluación de presiones de selección en maíz chulpi (Zea mays l.) para la obtención de un compuesto balanceado, en la parroquia Joseguango Alto, provincia de Cotopaxi, 2015 - Morales Yugcha, Alexis David (2016)
This research in the field phase was conducted in the locality Joseguango alto and selection work on site Seed Bank - Grain Andean Project, Technical University of Cotopaxi. Selection pressures was evaluated in corn seed chulpi UTC-003, to maintain a remnant seed, original population or Balanced Compound (CB). The following specific objectives were posed: Identify the best Percentage of selection pressure applicable, to form Compounds Balanced of chulpi corn. Was implemented a Randomized Complete Blocks Design with four treatments assessment in 1600 m2 applying (5, 10, 20 and 30) % of selection pressure to the original seed, using a stratification of sublot (SL) to the ears of the test selection parameters cob weight, number of seeds per cob and seeds weight per cob. The results in the selection pressures shows that there is no statistical significance in variables cob weight with an average of 81 g and a Coefficient of Variation (CV) of 9.12%....